Improving fifth- grade students’ learning outcomes using problem-based learning model in the integrated thematic learning - Diniyyah, Dian; Ningsih, Yarisda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
The study was motivated by the learning process that has not been student-cantered, students were less active in learning, teachers had not applied innovative group-based models, and student learning outcomes were still low. The approach used by researchers in this study was a combination of qualitative and quantitative approach. the method used in this study was classroom action research (CAR). This study was conducted in the first semester of the 2022/2023 school year. The subjects in this study were 23 students. The data source was the process and results of implementing integrated thematic learning with a problem-based learning model. The techniques used were observation, tests and non-tests. The results of the study showed that students’ learning outcomes increased from the learning activities in cycle I to cycle II. This study concluded that the problem-based learning model can improve student learning outcomes in integrated thematic learning.